Factors affecting clinical experience of nursing students in Malaysia: A cross-sectional study - Nurul N. H. Baba; Subhashini N. Govindan; Basirah A. Ghani; Duangta Shet; Y.S Pek (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Nursing education covers pathophysiology, nursing procedures, and compassionate care. Nursing students can apply theory and develop skills in the real world by participating in a supportive learning environment. For nursing students to effectively apply what they have learned in the classroom, they need a supportive clinical learning environment. However, some difficulties and impediments may prevent them from learning and having excellent clinical placement experiences. This study aims to identify factors affecting nursing students' clinical experience during clinical placement. MATERIALS AND METHODS: The respondents in this descriptive cross-sectional study were at Universiti Kuala Lumpur (RCMP) Diploma in Nursing students in Ipoh, Perak, who had more than two clinical placements at a public hospital. The time frame of the study was 6 months. Sociodemographic information and elements affecting clinical practice, such as perceptions of clinical experience, hospital settings, and clinical instructor aspects, were obtained by a self-administered questionnaire. A descriptive analysis and the Kruskal-Wallis test were used to obtain the study's outcome. RESULTS: Although the clinical placement demonstrated possibilities for learning, research has shown that the absence of instructors, equipment, and nursing staff has a negative impact on students' experiences. The study also discovered a substantial correlation between a student's semester and their clinical experience and between the clinical environment and the contributions of clinical instructors with P < 0.05. CONCLUSION: In conclusion, the study semester, clinical experience, clinical ambient characteristics, and instructors' contributions are strongly correlated. It suggests boosting academic-clinical collaboration, interprofessional collaboration, and student clinical experiences.